Arrested Pneumatization of the Sphenoid Sinus on Large Field-of-View Cone Beam Computed Tomography Studies - Mehrnaz Tahmasbi-Arashlow; Sevin Barghan; Jeffrey Bennett; Rujuta A. Katkar; Madhu K. Nair (MDPI AG, 2015)
Arrested pneumatization of the sphenoid sinus is a normal anatomical variant. The aim of this report is to define cone beam computed tomography (CBCT) characteristics of arrested pneumatization of sphenoid sinus in an effort to help differentiate it from invasive or lytic skull base lesions. Two cases are presented with incidental findings. Both studies, acquired for other diagnostic purposes, demonstrated unique osseous patterns that were eventually deemed to be anatomic variations in the absence of clinical signs and symptoms although the pattern of bone loss and remodeling was diagnosed as pneumatization of the sphenoid sinus by a panel of medical and maxillofacial radiologists following contrasted advanced imaging. It is important to differentiate arrested pneumatization of the sphenoid sinus from lesions, such as arachnoid granulations, acoustic neuroma, glioma, metastatic lesions, meningioma, or chordoma, to prevent unnecessary biopsies or exploratory surgeries that would consequently reduce treatment costs and alleviate anxiety in patients.